Does the force of gravity acts at a distance? - Janusz, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
The second Law of Newton's dynamics could be regarded as a research program: by investigating momentum change, one is able to obtain simple formulae for expressing the physical force. However, such a program is unrealistic because of the problem with defining the concept of inertial system. Einstein has solved this problem in his general theory of relativity. In this theory, Gravity is not a force but rather the geometry of the world. It does not act at a distance, but determines local motions of masses. Einstein's research program consisted in a bold hypothesis in the field of mathematical physics rather than in any mathematization of observational results. The second Law of Newton's dynamics could be regarded as a research program: by investigating momentum change, one is able to obtain simple formulae for expressing the physical force. However, such a program is unrealistic because of the problem with defining the concept of inertial system. Einstein has solved this problem in his general theory of relativity. In this theory, Gravity is not a force but rather the geometry of the world. It does not act at a distance, but determines local motions of masses. Einstein's research program consisted in a bold hypothesis in the field of mathematical physics rather than in any mathematization of observational results.